1979
DOI: 10.1007/bf00173811
|View full text |Cite
|
Sign up to set email alerts
|

Fields and plasmas in the outer solar system

Abstract: The most significant information about fields and plasmas in the outer solar system, based on observations by Pioneer 10 and 11 investigations, is reviewed. The characteristic evolution of solar wind streams beyond 1 AU has been observed. The region within which the velocity increases continuously near 1 AU is replaced at larger distances by a thick interaction region with abrupt jumps in the solar wind speed at the leading and trailing edges. These abrupt increases, accompanied by corresponding jumps in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 50 publications
6
33
0
Order By: Relevance
“…Voyager observations of B(R) between 1 AU and 5 AU have been discussed by Burlaga et al (1982). This paper extends that analysis to 1, 9.5 AU, and it complements the studies based on Pioneer 10 and 11 observations made beyond 1 AU during a different part of the solar cycle (Smith, 1974 and1979;Wolfe, 1979 and1977;and Rosenberg et al, 1978). These early measurements indicated that the large scale field could be described by Parker's spiral field model (Parker, 1963), which gives Bo = B p (R) = A(1 + R ) 1/2 /R 2 .…”
Section: Introductionsupporting
confidence: 54%
“…Voyager observations of B(R) between 1 AU and 5 AU have been discussed by Burlaga et al (1982). This paper extends that analysis to 1, 9.5 AU, and it complements the studies based on Pioneer 10 and 11 observations made beyond 1 AU during a different part of the solar cycle (Smith, 1974 and1979;Wolfe, 1979 and1977;and Rosenberg et al, 1978). These early measurements indicated that the large scale field could be described by Parker's spiral field model (Parker, 1963), which gives Bo = B p (R) = A(1 + R ) 1/2 /R 2 .…”
Section: Introductionsupporting
confidence: 54%
“…Those features, which may have considerable and as yet unknown effects on our understanding of drift-dominated cosmic ray transport, are the effects of complicated current sheet topologies, variable solar wind speeds, and large-scale magnetic field intensity perturbations. For example, high-speed solar wind streams restructure the interplanetary medium by overtaking and interacting with slower speed solar wind as they propagate outward from the sun, generating corotating interaction regions (CIRs) [e.g., Smith and Wolfe, 1979] or merged Measurements of cosmic rays with kinetic energies greater than energy threshold. interaction regions [e.g., Burlaga et al, 1983;Burlaga, 1984].…”
Section: Discussionmentioning
confidence: 99%
“…The leading edge of the interaction region is characterized by an increase in plasma density, temperature and magnetic field intensity and the trailing edge by decrease in these quantities (Smith and Wolfe, 1979). The solar wind speed increases at both edges.…”
Section: Cir Eventsmentioning
confidence: 99%